Engineering of a third-generation chimeric antigen receptor with specificity for HLA-A2 for use in regulatory T cell therapy - Wright, S (2022)
Background: Current pharmacologic regimes of immunosuppression for allogeneic transplant recipients increase vulnerability to cancers and infections due to their systemic mode of action, in addition to side effects such as organ toxicity. Furthermore, daily medication regimes pose a significant burden to the patient. Cellular therapy has been proposed as an alternative, and clinical trials have shown promising results for the efficacy of regulatory T cells – a naturally-occurring subset of T cells responsible for maintaining immune homeostasis – for preventing graft rejection in kidney patients. Genetic engineering has led to the development of Chimeric Antigen Receptors (CARs); these are customizable receptors that can be expressed in therapeutic cells to confer specificity for an antigen of choice. Pre-clinical models have shown the superiority of CAR-expressing Tregs over polyclonal Tregs at preventing allograft rejection, as well as their preferential homing towards the target antigen, and it is envisaged that CAR-Tregs could replace standard drugs in the clinic.